The Role of Material/Energy Resources and Dematerialisation in Economic Growth Theories - Robert U. Ayres; Jeroen C.J.M. van den Bergh (Tinbergen Institute, 2000)
The nature of energy and material resources in an endogenous growththeory framework isclarified. This involves three modifications of the conventionaltheory. Firstly, multiple feedbackmechanisms or “growth engines” are identified. Secondly, a productionfunction distinguishesbetween resource use, technical efficiency and value creation.Thirdly, the impact of the cost ofproduction through demand on growth is accounted for. A formal modelis analytically solvedunder a condition of a constant growth rate. Given model complexity,numerical experiments areperformed as well, providing relevant insights to the academic andpolitical debates on`environmental Kuznets curves' and `dematerialization'.
Keywords: O11; O33; O41; Q32; Q43; 330; dematerialization; environmental Kuznets curve; feedback mechanisms; production function specification; resource scarcity; value creation; Wachstumstheorie; Ressourcenökonomik; Theorie